Dual-class recapitalizations as antitakeover mechanisms - Jarrell, Gregg A.; Poulsen, Annette B. (Journal of Financial Economics, 1988)
We report evidence on shareholder wealth effects of 94 firms recapitalizing with dual classes of common stock with disparate voting rights. We find significant, negative abnormal stock price returns at the announcement of the dual-class recapitalization. When we consider recapitalizations separately announced since the NYSE imposed a moratorium is June 1984 on the delisting of companies with dual classes of equity, we find significant, negative abnormal returns as compared with insignificant returns in the earlier period. Those firms recapitalizing from June 1986 through May 1987 experienced the most significant negative returns observed.